2007
DOI: 10.1589/jpts.19.197
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Expiratory Muscle Training on Pulmonary Function in Normal Subjects

Abstract: Abstract. The objective of the present study was to investigate the effects of expiratory muscle training (EMT) on pulmonary function, including peak cough flow (PCF), by administering EMT at a natural or fast flow rate to healthy volunteers. Subjects comprised 33 healthy volunteers randomly divided into 3 groups: EMT at a natural expiratory flow rate (NFR group); EMT at a fast expiratory flow rate (FFR group); and no EMT (Control group). For the NFR and FFR groups, subjects trained using a device for expirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…PCF was assessed using a peak flow meter (Micro Medical, Cambridge, UK). PCF has been used as a measure of huff strength, and the effectiveness of airway clearance depends largely on PCF 6 ) .…”
Section: Methodsmentioning
confidence: 99%
“…PCF was assessed using a peak flow meter (Micro Medical, Cambridge, UK). PCF has been used as a measure of huff strength, and the effectiveness of airway clearance depends largely on PCF 6 ) .…”
Section: Methodsmentioning
confidence: 99%
“…The application of an inspiratory load is a method used for inspiratory muscle training (IMT) (Hostettler et al, 2011); it helps to increase endurance and respiratory muscle strength in order to improve lung function (Sasaki, 2007), functional capacity (Shakouri et al, 2015), and efficacy in bronchial airway clearance (Oliveira et al, 2009). Three IMT techniques reported in literature are more commonly used: voluntary isocapnic hyperpnea, flow resistive loading, and pressure threshold loading (McConnell and Romer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, these group differences were not significant. Previous studies demonstrated that smaller lung resection areas are associated with greater differences in respiratory muscle strength before and after surgery 8 , 9 ) . We speculate that respiratory muscle strength did not differ significantly among our groups because all subjects had undergone video-assisted thoracoscopic surgery, which requires a minimal incision in the respiratory muscles interacting with the chest wall.…”
Section: Discussionmentioning
confidence: 97%